Strategi Kebijakan Pendidikan Jenjang Menengah di Kalimantan Tengah: Analisis Deskriptif Menuju Program Satu Keluarga Satu Sarjana - Yunanae Eka Asi Ilas (CV. Green Publisher Indonesia, 2026)
The phenomenon of low opportunities for secondary school opportunities in Central Kalimantan is marked by many residents in Central Kalimantan, especially in rural areas, not continuing to high school/equivalent in the midst of the challenges of achieving the One Family One Undergraduate Program in Central Kalimantan. The average length of school for residents 15 years and older is 9.36 years or equivalent to grade IX junior high school/equivalent (Central Kalimantan Education Statistics in 2025, BPS Central Kalimantan Province, 2026). This study uses a qualitative approach with descriptive analysis. Data processing techniques use taxonomic analysis, data collection techniques with documentation techniques. The approach used in this study uses the 8-step method approach Bardach (2012). Determination of the root of the problem by ultrasound (Urgency, Seriousness, Growth) method. Then the determination of policy selection using the Weighted Scoring Model (WSM) method. The Weighted Scoring Model is an evaluation method used to assess and select policy alternatives by calculating the score of each policy alternative using the weighting of predetermined criteria. This study aims to provide recommendations to the Central Kalimantan provincial government to overcome the low educational opportunities at the secondary level. So that the One Family One Undergraduate Program can be achieved. Key findings of this study indicate that the low opportunities for accessing secondary education in Central Kalimantan are caused by both natural and artificial factors. The natural factors include geographical, topographical, hydrological, geological, and demographic conditions. Meanwhile, the artificial factors include the lack of educational facilities and infrastructure, as well as insufficient supporting infrastructure such as road and bridge transportation systems. The recommended policy for the Central Government is to establish a Ministerial Regulation of Primary and Secondary Education concerning the implementation of education in remote areas. For the Provincial Government of Central Kalimantan, the recommended policy is the implementation of a “Flying Teacher Program” for the secondary education level